ANALISIS KEBUTUHAN PENGEMBAGAN MODEL PEMBELAJARAN BBM3 UNTUK MENINGKATKAN METAKOGNISI MAHASISWA - Andi Suhandi; Issaura Sherly Pamela (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2019)
This study aims to analyze the needs of developing BBM3 learning models (Thinking, Planning, Implementing, Monitoring, Evaluating) to improve student metacognition. The research is conduct by survey method in the Elementary School Teacher Education Study Program (PGSD), Teacher Training and Education Faculty (FKIP), Jambi University. The research subjects were 115 3rd semester students and 4 PGSD lecturers. The objects studied were curriculum analysis of PGSD FKIP UNJA, students' metacognition abilities, the learning process that has been applied so far especially in improving student metacognition, and lecturers' and students' responses to the development of BBM3 learning models. The research instruments used to obtain data were questionnaires and tests. Data obtained from these instruments were analyzed descriptively. The analysis results obtained are the PGSD FKIP curriculum in UNJA demanding students think about thinking, known as metacognition, not all lecturers invite students to monitor and evaluate learning continuously. The class average of the students' metacognition ability tests was in the poor category with a score of 32.87. The learning process so far has focused on improving teaching skills in elementary schools, activeness, and student character, not all lecturers have explored metacognition abilities, with the category sometimes. Lecturers interested in the BBM3 learning model with the category of strongly agree. The conclusion of this research is the need for the development of BBM3 learning is very high, so this learning model needs to be developed.